Pengaruh Return on Asset, Current Ratio dan Debt to Equity Ratio Terhadap Pertumbuhan Laba pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2018-2022 - Andi Mustika Amin; Burhanuddin Burhanuddin; Muh Fatwa Baso (Universitas 45 Surabaya, 2024)
This study aims to determine the effect of Return On Asset, Current Ratio and Debt To Equity Ratio on profit growth in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. This type of research is an associative approach. The population in this study is all food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX), namely a total of 33 companies, while the sample in this study was selected using purrposive sampling, as a result of which the sample used by 10 food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) met the criteria. The data collection technique is carried out by documentation techniques. The results of the study show that partially Return On Asset has a positive effect on profit growth in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period, partially the Current Ratio has a negative effect on profit growth in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period, partially, the Debt To Equity Ratio has a positive effect on the growth of profit in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period and simultaneously Return On Asset, Current Ratio and Debt To Equity Ratio both have a significant effect on profit growth in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period.